1H‐MR spectroscopy characterization of the adipose tissue associated with colorectal tumor. Issue 2 (30th May 2013) - Mosconi, Elisa; Minicozzi, Annamaria; Marzola, Pasquina; Cordiano, Claudio; Sbarbati, Andrea
<x xml:space="preserve">Abstract</x> Purpose To investigate colorectal tumor by looking at the lipid tissue around the lesion. Adipose tissue is not only an inert storage system for excess calories, but is involved in several pathological processes linked to tumor development. Materials and Methods We obtained 24 colorectal specimens after surgical excision from patients affected by colorectal cancer at different tumor stages. 1H‐MR spectoscopy (MRS) spectra were collected from two voxels, in proximity of the lesion and far from it, in each specimen with a preclinical scanner. We differentiated patients by pathological tumor stage, and we compared the chemical composition of adipose tissue between patient groups, both close the tumor and far from it. Results Monounsaturated fatty acids (MUFA) close the lesion are increased at higher tumor stages, while MUFA far from the lesion do not follow this trend. This study is really explorative due to the small numbers of subjects and we are cautious on the interpretation of the results. However, the approach of the present work allows a further insight in the tumor characterization. Conclusion Looking at the lipid tissue around a lesion through 1H‐MRS can return important information regarding its genesis and development. J. Magn. Reson. Imaging 2014;39:469–474. © 2013 Wiley Periodicals, Inc.